A New Method Of Speed Sensorless Control For Permanent Magnet Synchronous Motor - Samat, Ahmad Asri Abd (2019)
Permanent magnet synchronous machine (PMSM) drives have been applied in a variety of industrial applications which require fast dynamic response and accurate control over wide speed range. However, it is important to get the accurate rotor position in order to control the PMSM drives efficiently. Therefore, speed sensorless control becomes an alternative approach due to its ability of dynamic response at very low frequencies to detect the rotor position and motor speed, which eliminates the use of traditional methods, such as optical encoders mounted shaft, resolver or hall sensor. There are many challenges to design speed sensorless vector control of PMSM operating in wide speed range, which cover low speed and high speed operation. To deal with the above-mentioned problem, a new speed sensorless control is proposed. This new speed sensorless control is based on model reference adaptive system (MRAS) with a new adaptation scheme. It was designed to replace the conventional technique which is proportional-integral controller. This new technique is based on Takagi Sugeno Fuzzy Inference System (TS-FIS). This new method can overcome the problem of tuning parameters in the traditional method when there is a change in the motor condition such as variation of speed. The performance of the proposed scheme is validated in Matlab/Simulink and obtained results are compared with conventional scheme. A simulation using MATLAB/Simulink software is conducted to investigate the feasibility of the proposed algorithm. DSpace is deployed for algorithm implementation. The analysis is carried out by comparing the simulation and hardware implementation in different cases of motor conditions. It shows that the proposed method can track the motor speed and rotor position angle accurately with minimum error which is almost 0 rad. Besides that, tests results for both simulation and experimental work, demonstrates the MRAS based on TS-FIS is capable of effectively and accurately locating the motor speed and rotor position angle in various conditions of speed with the given load to the motor for PMSM. Comparison with two other methods used in the adaptation from the previous researchers shows that MRAS based on TS-FIS is capable of detecting the rotor position efficiently, by giving 0 rad reading for rotor position error in steady state and transient conditions. As well as the speed error which gives ±3 radian for both states.